Incentive Package, Employee’s Productivity and Performance of Real Estate Firms in Nigeria - Oloke, Olayinka C.; Oni, Abiodun S.; Babalola, Daniel O.; Ojelabi, Raphael A. (European Scientific Journal, ESJ, 2017)
The level of motivation received by an employee as reflected in the satisfaction with the base pay package and other incentives goes a long way to influencing the employees’ attitude to work, loyalty, performance and job satisfaction. Employee’s motivation and organization performance has been investigated across different fields and economic sectors. This study takes it further by examining incentive package, employees and organization productivity in real estate firms in Nigeria. Panel survey approach was adopted and three questionnaires administered in each of the one hundred and seventeen (117) estate firms in Ikeja, Victoria Island and Lekki Area of Lagos State. Respondents were two employees and one other in employers’/management capacity. Descriptive tools such as frequency and percentage were used to identify and determine the proportion of firms that make use of incentive package/option while a 5-point Likert scale and ranking were used to determine and rank the options in order of importance among these firms. Panel data regression model was used to determine the strength of relationship between firms’ performance/productivity and incentives whilst holding other factors constant. Findings showed amongst others that there is strong positive correlation between incentive and employee productivity, employees are largely dissatisfied with the incentives offered by majority of estate firms and that incentive package is not the most important determinants of performance in real estate firms. The study therefore concludes that employers in real estate firms pay attention to other factors identified and review remuneration and incentive package to boost the morale of their employees for better performance.